2015
DOI: 10.1136/jech-2015-205598
|View full text |Cite
|
Sign up to set email alerts
|

Social inequality in pre-pregnancy BMI and gestational weight gain in the first and second pregnancy among women in Sweden

Abstract: Lower educated women had the largest BMI increase between pregnancies, and these inequalities were greatest among women with excessive GWG in the first pregnancy. The importance of a healthy pre-pregnancy BMI, appropriate GWG and a healthy postpartum weight should be communicated to all women, which may assist in reducing existing social inequalities in body weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
3
19
0
Order By: Relevance
“…This indicates that overweight and obese women are at higher risk of excessive GWG, which may increase the risk of complications during pregnancy and delivery. This is in line with previous findings of excessive GWG in different BMI categories according to IOMs guidelines (Holowko et al 2015 ).…”
Section: Discussionsupporting
confidence: 93%
“…This indicates that overweight and obese women are at higher risk of excessive GWG, which may increase the risk of complications during pregnancy and delivery. This is in line with previous findings of excessive GWG in different BMI categories according to IOMs guidelines (Holowko et al 2015 ).…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence was higher in pregnant women with elementary education (vs. high school or university) and women born in foreign countries [ 2 ]. Women with lower education also had the largest BMI increase between pregnancies [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…One found that education was inversely associated with excessive GWG among healthy women having either their first or second singleton birth (Holowko et al, 2015). Another found that among women with a healthy pre-pregnancy BMI, those with an elementary or secondary education had greater odds of excessive GWG than women with higher education (Holowko, Mishra, & Koupil, 2014).…”
Section: Introductionmentioning
confidence: 99%